2011
DOI: 10.1111/j.1574-695x.2011.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation and envelope protein analysis of internalization defective Brucella abortus mutants in professional phagocytes, RAW 264.7

Abstract: Brucella abortus is a facultative intracellular bacteria that replicates within a macrophage without producing any classical virulence factors. It can become internalized to cells by zipper-like and/or swimming internalization mechanisms. However, the bacterial proteins involved in internalization remain unclear. To define these bacterial proteins, random insertion mutants of B. abortus were generated by the Tn5 transposome complexes. In all, 132 mutants were screened, cellular internalization-defective mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…Furthermore, these results contradict previously published data, which described this antigen as of no diagnostic value (Xin et al, 2013). However, data from other studies (Cloeckaert et al, 2001;Liu et al, 2011;Cha et al, 2012) showed that the OMP28-based I-ELISA had high sensitivity and specificity in the diagnosis of brucellosis in bovine sera, conforming to our results. Fig.…”
Section: Immunoreactivity Of Romp28 Of Brucella Sppcontrasting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, these results contradict previously published data, which described this antigen as of no diagnostic value (Xin et al, 2013). However, data from other studies (Cloeckaert et al, 2001;Liu et al, 2011;Cha et al, 2012) showed that the OMP28-based I-ELISA had high sensitivity and specificity in the diagnosis of brucellosis in bovine sera, conforming to our results. Fig.…”
Section: Immunoreactivity Of Romp28 Of Brucella Sppcontrasting
confidence: 57%
“…have been the focus of vaccine development and the diagnosis of brucellosis (Cloeckaert et al, 2001;Gupta et al, 2010;Ko et al, 2012). OMP28 is considered as one of the outer membrane proteins of Brucella (Cha et al, 2012) and has been identified as an important diagnostic antigen in brucellosis (Seco-Mediavilla et al, 2003;Poester et al, 2010). OMP28 is highly conserved among B. abortus, B.…”
Section: Introductionmentioning
confidence: 99%
“…The internalization defective mutant C10, C29, D6 and D7 were derived from our previous study [8]. Brucellae were cultured in Brucella broth or agar (Difco, USA), and Kanamycin (30 μg/ml) was used when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…RAW 264.7 cells were infected with each Brucella strain as described previously [8]. Briefly, RAW 264.7 cells were seeded (5 × 10 6 cells per flask) in T75 flasks one day before infection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation